2011
DOI: 10.1093/bioinformatics/btr391
|View full text |Cite
|
Sign up to set email alerts
|

Integration and visualization of host–pathogen data related to infectious diseases

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Additionally, analysis of a survey conducted by Bassil and Keller [67] indicated that users in academic settings are nearly twice as sensitive to the cost of a new tool as are users in industry. This finding is consistent with many studies exploring or advocating for open-source and web-based infectious disease visualization tools to overcoming cost and resource barriers [62, 70, 73, 77, 79, 84-86]. Moreover, these preferences mirror key themes from Section 3.1, namely user trust, tool credibility and transparency.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Additionally, analysis of a survey conducted by Bassil and Keller [67] indicated that users in academic settings are nearly twice as sensitive to the cost of a new tool as are users in industry. This finding is consistent with many studies exploring or advocating for open-source and web-based infectious disease visualization tools to overcoming cost and resource barriers [62, 70, 73, 77, 79, 84-86]. Moreover, these preferences mirror key themes from Section 3.1, namely user trust, tool credibility and transparency.…”
Section: Resultssupporting
confidence: 88%
“…Cognitive overload, wherein a user is presented with more information than they are able to successfully process, was addressed in several studies. This highlights the unique challenge of displaying complex and large datasets without reducing usability reaching the technical limits of the platform or the cognitive limits of the user [69, 70]. Strategies to minimize cognitive overload were less defined, although Herman [69] suggested human-centered design as a means of improving data visualization interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations